Synthesis of Al Doped ZnO Thin Films from ZnO Powder Mixed with Al Wire Targets by Using Asymmetric Bipolar Pulsed-dc Magnetron Sputtering System - Phimpabutra, Nuwat (Naresuan University Journal: Science and Technology (NUJST), 2021)
The thin films of Al doped ZnO were grown on glass substrate at room temperature from three targets of Al wires mixed ZnO powder with sputtered area ratio of Al wire to ZnO powder of 0%, 5% and 15% by using an asymmetric bipolar pulsed-dc magnetron sputtering system. The effect of Al doping on structural, electrical and optical properties of ZnO thin film were investigated. The X-ray diffraction patterns showed that Al doped ZnO thin film are polycrystalline of hexagonal wurtzite structure with preference orientation in (002) plane. By increasing Al wires area ratio from 0% to 15%, the resistivity of the films was decreased from 231.45 mWcm to 5.20 mWcm. The optical transmittance spectra of all films show that the maximum value reaches to 90% in the visible region.  These results showed that the thin films obtained from Al wire mixed ZnO powder target by using an asymmetric bipolar pulsed-dc magnetron sputtering system was successfully deposited on glass substrate, the resistivity can be decreased by increasing Al content with low effect on optical transparent properties of the film.  Keywords: Al doped ZnO, optical transmittance, resistivity, sputtering, ZnO films